Kandungan Formalin pada Ikan Asin yang Dijual di Pasar Tradisional Kota Makassar Studi Kasus: Pasar Terong, Pa’baeng-baeng dan Toddopuli - Ruslan La Ane; Makmur Selomo; Ingri Yunus Teda (HIGIENE: Jurnal Kesehatan Lingkungan, 2016)
Salted fish is one of dishes that has long been known and favored by Indonesian people. Na-tionally, salted fish have an important position in the Indonesian fishery products, approximately 65% of fishery products are still processed and preserved by salting. In fact, there are producers and trad-ers who fraudulently adding ingredients harmful to health which is prohibited from use in foods such as formalin. The use of formaldehyde as a food preservative has been known to be detrimental to health, but its use continues to rise due to the price is relatively cheap and easily obtained. This study aims to identify formaldehyde content contained in salted fish sold in the traditional market of Ma-kassar City.This study was an observational study with descriptive approach. A total of 31 samples of dried fish were collected using purposive sampling of seven salted fish seller in three traditional markets, namely Terong, Pa’baeng-baeng, and Toddopuli traditional market. Formaldehyde test kits used to measure the levels of formaldehyde in samples of dried fish.The results of this study indicate that all (100%) samples of salted fish sold in the three tradi-tional markets of Makassar positive for formaldehyde levels ranging from 10 mg, 40 mg and some even up to 200 mg. Based on the regional origin of salted fish suppliers, mostly from the area of Kendari, Selayar, and Paotere. While the rest comes from the region Pangkep Galesong, Kalimantan and Mandar. Salted fish samples that contain high levels of formaldehyde (200 mg) was found on sell-er-1 in the Terong market supplied from the area of Kendari and Kalimantan. According to PERMEN-KES No. 1168 / Menkes / Per / X / 1999 on Food Additives states that formaldehyde is one additional ingredient which is prohibited inserted into the food that should not be present in food, albeit in low levels.The study concluded that the entire samples of dried fish examined does not meet health re-quirements established by PERMENKES No. 1168 / Menkes / Per / X / 1999 and therefore declared as unsafe for consumption.Keyword: Formalin, salted fish, traditional market, Makassar